2020
DOI: 10.1016/j.gore.2020.100656
|View full text |Cite
|
Sign up to set email alerts
|

Acute extraperitoneal spontaneous bladder rupture in cervical cancer patient undergoing chemoradiation: A case report and review of the literature

Abstract: Highlights Spontaneous bladder ruptures have only been reported intraperitoneally, and years after the cessation of therapy. Extraperitoneal bladder rupture can occur with radiation therapy in treatment of cervical cancer. Improved reporting of toxicity is needed to identify types of genitourinary toxicity seen with modern chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Once exclusion criteria were applied to the abstracts, 352 studies remained for full‐text review. After again applying the exclusion criteria to the full texts, a total of 278 manuscripts remained and were included in the final review […”
Section: Resultsmentioning
confidence: 99%
“…Once exclusion criteria were applied to the abstracts, 352 studies remained for full‐text review. After again applying the exclusion criteria to the full texts, a total of 278 manuscripts remained and were included in the final review […”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic methods for SBR are cystography or cystoscopy, and confirming the presence of a fistula is most useful [25][26][27][28][29][30][31]. CT can demonstrate the findings of SBR in the presence of contrast medium in the abdominal cavity after intravenous contrast medium injection [32] and abnormalities of the bladder wall on CT [33].…”
Section: Discussionmentioning
confidence: 99%
“…A literature search using the terms "spontaneous urinary bladder rupture", "radiotherapy", and "peritonitis" in PubMed showed that only 25 cases (including this case) of generalized peritonitis, caused by SBR after radiotherapy, have been reported, and the available information is summarized in Table 1 [25][26][27][28][29][30][31][32]35,36,[45][46][47][48][49][50][51][52][53][54][55][56]. Previously reported patients included 5 men and 20 women, ranging from 27 to 82 years (median: 64 years) (3 cases unknown).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors known to cause SBR include inflammation, infection, pelvic irradiation, bladder tumor, and urinary retention [2] . However, as shown in Table 1 , a literature search using the terms “spontaneous bladder rupture” and “cervical cancer” in PubMed identified only 10 English articles describing a total of 15 cases of SBR in women with a history of cervical cancer [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . Out of them, 14 cases were complications of pelvic radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“… (2012) 44 IB RT followed by Hysterectomy 5 years Abdominal pain Bacterial peritonitis Antibiotics NA Intraperitoneal RT Neurogenic bladder Bladder repair No recurrence Shin JY, et al [9] . (2014) 55 NA Hysterectomy + Adjuvant RT 13 years Abdominal pain Distension Oliguria Acute abdomen Renal failure Hemodialysis Nephrostomy 14 days Intraperitoneal RT-induced urethral stricture Bladder repair No recurrence Welp A, e al [10] . (2020) 27 IIIC1(FIGO2018) Definitive RT 0 days (Last day of RT) Abdominal pain Nausea/Vomiting SBR Indwelling catheter 0 day Extraperitoneal RT Indwelling catheter (10 weeks) No recurrence Iwasaki H, et al [11] .…”
Section: Introductionmentioning
confidence: 99%